Peningkatan Kesadaran Hukum di Kalangan Remaja melalui Pembentukan Kader Sadar Hukum Pada Pramuka di Kab. Jombang: Pengabdian - Herini Siti Aisyah, Rr.; Suheryadi, Bambang; Shomad, Abd; Adhipramana, Fikri; Arnanda Mahantika, Nacha; Savero Rianda, Juan (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
The purpose of this program is to foster legal literacy, build disciplined character, and strengthen the role of youth as agents of change within schools and communities. The activities are carried out through legal counseling, interactive training, case simulations, and the use of digital media as an educational tool. Through these activities, participants experience an increased understanding of basic law, citizens’ rights and obligations, and the ability to analyze legal issues in their surroundings. The program also encourages participants to confidently share legal information with their peers. The Scout-Based Legal Awareness Cadre Model has proven effective as it integrates character development, leadership, and national values with practical legal education, creating a generation of young people who are legally aware, critical, and responsible.